2022
DOI: 10.1136/bmjopen-2022-061465
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding patient partnership in health systems: lessons from the Canadian patient partner survey

Abstract: ObjectivesTo examine the sociodemographic characteristics, activities, motivations, experiences, skills and challenges of patient partners working across multiple health system settings in Canada.DesignOnline cross-sectional survey of self-identified patient partners.SettingPatient partners in multiple jurisdictions and health system organisations.Participants603 patient partners who had drawn on their experiences with the health system as a patient, family member or informal caregiver to try to improve it in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 14 publications
(33 reference statements)
3
21
0
1
Order By: Relevance
“…Across data sources, evaluation participants commonly mentioned the diversity of gender, ethnic, and disciplines among service providers as a strength of EMBOLDEN's SGC. Similar to other patient partner populations, most evaluation survey respondents were female and welleducated [55,56], but our results showed some diversity of age, and ethnicity and with some representation from visible minority; lesbian, gay, bisexual, transgender; new immigrant; and disability communities. This diversity is notable considering the lack of age, ethnicity, and birth country diversity among patient partner populations in Canada and the UK [55,56].…”
Section: Structuresupporting
confidence: 78%
See 1 more Smart Citation
“…Across data sources, evaluation participants commonly mentioned the diversity of gender, ethnic, and disciplines among service providers as a strength of EMBOLDEN's SGC. Similar to other patient partner populations, most evaluation survey respondents were female and welleducated [55,56], but our results showed some diversity of age, and ethnicity and with some representation from visible minority; lesbian, gay, bisexual, transgender; new immigrant; and disability communities. This diversity is notable considering the lack of age, ethnicity, and birth country diversity among patient partner populations in Canada and the UK [55,56].…”
Section: Structuresupporting
confidence: 78%
“…Interestingly, there was limited discussion of trust, and few concerns brought up about power-sharing by evaluation participants. This is notable considering that a recent Canadian study noted power imbalances as the most commonly experienced barrier for patient and public research partners working in health systems [55], and the emphasis in the literature on trust and the effort required to address power differences between researchers and research partners [67,68]. Previous research has shown that efforts to be inclusive, such as break-out groups, and an informal environment can reduce power differentials between researchers and research partners and increase trust [60,69].…”
Section: Processmentioning
confidence: 99%
“…We engaged in patient partnership in the current study, incorporating two research team members with lived experience of the healthcare system as caregivers and more saliently, a long history of working as patient partners (MAL, CC). MAL and CC are cofounders of the Patient Advisors Network, a national peer-led patient partner network [ 23 , 24 ]. The aim of involving patient partners was to ensure that our research was relevant and resonant with this stakeholder community.…”
Section: Methodsmentioning
confidence: 99%
“…CC participated in the origination of the idea and application for funding, and both MAL and CC attended research team meetings and provided regular written and oral feedback as the project developed. MAL and CC continue to participate in similar ways (strategic planning, operational and interpretive guidance) on the broader programme of research on patient partnership which this study involves, including a nationwide survey of patient partners and a qualitative study of patient partners and organizational staff who work with patient partners [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…This may be reflective of the state of the patient and caregiver engagement field, where the considerable focus has been placed on the importance of engaging in an inclusive manner and in pursuit of equity goals, but significant gaps remain in turning principles into action. 21,22 We anticipate that this section of our toolkit will expand over time as more attention is paid to this area.…”
Section: Limitationsmentioning
confidence: 99%